Error analysis of descriptive writings by pre-service EFL teachers: A case study in Indonesia - Siti Lestari; Rahmawati Sukmaningrum; Eka Setia Widhianto (SALEE: Study of Applied Linguistics and English Education, 2022)
This research investigates pre-service EFL teachers’ writing proficiency by analyzing errors made in their descriptive essays. Conducted in one teacher training university in Indonesia, 40 randomly selected writing products assigned for the Writing course of 160 pre-service teachers, who are novice writers, were qualitatively analyzed. The result of the analysis showed that there were sentence fragments with 21 times or 42 %. It means that sentence fragment was the most dominant error done by students. Sentence fragment appeared due to the absence required in a complete sentence. Run-on sentence and comma splice existed 16 times or 32 %. Run-on sentences and comma splices appeared due to the wrong in combining two independent clauses. Choppy sentence were found 10 times or 20 % due to the use of too many short sentences, sometimes often repeating the same word at the beginning of a sentence. Stringy sentence were identified 3 times or 6 % of the whole essays due to the use of too many clauses with connected words. These clauses strung together forming one very long ineffective sentences. The findings are expected to reveal a comprehensive evaluation of writing proficiency of pre-service teachers and call for students, teacher educators, and policy makers to more concern with this crucial issue.